Pre- and postharvest application of alternative means to control Alternaria Brown spot of citrus. (July 2019) - Garganese, Francesca; Sanzani, Simona Marianna; Di Rella, Danila; Schena, Leonardo; Ippolito, Antonio
Abstract: Alternaria brown spot (ABS) is one of the main diseases of mandarins and their hybrids. Its control is based on fungicide applications, but their use is facing difficulties related to the development of resistant pathogen strains and adverse effects on animals, humans and the environment. The present study was undertaken to find feasible alternative solutions to control ABS, by testing the effectiveness of phenolic compounds and alternative formulations present on the market. They were tested in vitro and in vivo on a laboratory scale and then in semi-commercial conditions. Umbelliferone was the most effective phenolic compound in controlling by 86% ABS on mandarins cv. Fortune in semi-commercial conditions. Its effect seemed related to the ability of inducing resistance in the host. Whereas among the formulations, chitosan-based HendophytPS and salt-based FortisolCaPlus gave the best results in field-scale trials, with a reduction of disease incidence by 59–63 and 54–75% on fruit and leaves, respectively, as compared to the control, being the effect similar to that obtained by chemical controls. The formulations showed mainly to induce host resistance. The application of proposed alternative treatments, singly or in a combined strategy, might represent an interesting substitute to synthetic fungicides against ABS. Highlights: We tested phenolic compounds and alternative formulations against Alternaria brown spot. In vitro and in vivo tests on a laboratory scale and semi -commercial conditions were performed. Umbelliferone was the most effective phenolic compound; it seemed to induce host resistance. Hendophyt and Fortisol were the most effective formulations, comparable to chemical controls. These alternatives, singly or in a combined strategy, might be effective against the disease.